Salary Issues and Strategic Management: A Systematic Literature Review - Rao Alvaro Alvino; Muchammad Rizqi; Rafi Untoro; Muhammad Faddly; Jordans Kencana; Yang Junfeng (International Journal of Management and Economic Research (IJOMER), 2025)
Strategic management plays a crucial role in addressing salary issues within organizations, especially in balancing internal equity and market competitiveness. This study aims to analyze how strategic management practices can be employed to resolve salary-related challenges, such as wage disparity, employee dissatisfaction, and retention problems. Utilizing a mixed-methods approach, this research combines quantitative data collected through structured surveys with qualitative insights from in-depth interviews with HR managers and employees across multiple industries. The results indicate that companies implementing clear compensation strategies aligned with performance metrics, job evaluations, and market standards experience higher employee satisfaction and organizational commitment. Moreover, strategic salary planning contributes to reduced turnover rates and improved employee morale. The study concludes that a well-integrated strategic management approach in compensation policy not only addresses salary issues effectively but also supports long-term organizational sustainability. Recommendations include continuous salary benchmarking, transparent communication, and strategic alignment between HR policies and business goals.